Fallacies in English Department Students’ Claims: A Rhetorical Analysis of Critical Thinking - Rohmani Nur Indah; Agung Wiranata Kusuma (Jurnal Pendidikan Humaniora, 2015)
Abstract: This study focuses on the fallacies found in English department students’ claims of fact, value and policy. It employs qualitative design as the object is the real reflection of critical thinking in the form of writing to understand the fallacies varieties.  The data are in the form of the sentences in the claims written by the students of UIN Maulana Malik Ibrahim Malang who took critical writing course. On claims of fact, the fallacies found include hasty generalization, irrelevancy, slippery slope, oversimplification and begging the question. Regarding pathos, the fallacy type covers ad populum, appeal to emotion premises and red herring. Meanwhile the ethos fallacy occurs in straw man only. On claims of value, more faulty reasoning is found compared to the discussion on the topics which are considered less familiar. In the logos fallacy for instance, the whole types of fallacy are found. The pa-thos found involves appeal to emotion premises and red herring. While the ethos fallacy occurs in appeal to authority and ad hominem. On claims of policy, the similar tendency of ethos is also found while the pathos existing is in the form of appeal to emotion premises. Key Words: fallacy, claims, logos, ethos, pathosAbstract: Penelitian ini mengkaji lompatan nalar dalam karangan argumentatif berjenis faktual, nilai dan kebijakan. Rancangan yang digunakan kualitatif dengan objek refleksi berpikir kritis dalam tulisan untuk memahami lompatan nalar yang ditemukan. Data penelitian berupa kalimat dalam klaim yang ditulis mahasiwa UIN Maulana Malik Ibrahim Malang pada mata kuliah menulis kritis. Pada klaim fak-tual, lompatan nalar meliputi generalisasi langsung, tanpa kaitan, terpelintir, penyederhanaan dan penuh pertanyaan. Dalam hal patos, lompatan nalar meliputi simbol umum,emotif dan pengalihan isu. Adapun lompatan dalam etos meliputi penyepelean opini saja. Dalam klaim nilai, terjadi lebih banyak lompatan nalar pada topik yang bersifat kurang umum. Pada logos, seluruh jenis lompatan nalar teri-dentifikasi. Adapun patos yang muncul yaitu pernyataan emotif dan pengalihan isu. Lompatan etos terjadi pada keberpihakan isu dan serang opini. Dalam klaim kebijakan, lompatan etos juga memiliki kecenderungan yang sama dan pada patos melibatkan penyataan emotif.Kata kunci: lompatan nalar, klaim, logos, etos, patos